Impact of financial inclusion on the effectiveness of interest rate channel of monetary policy transmission in West Africa/ Ridwan Olamilekan Dauda - Dauda, Ridwan Olamilekan (Universiti Teknologi MARA Selangor, 2022)
Monetary policy has been identified as an indispensable tool for macroeconomic stabilization. The transmission of monetary policy is conditioned on the effectiveness of the intermediate targets of which interest rate, exchange rate depreciation, and money growth are essential. Many factors have been shown to affect monetary policy, of which the role of financial inclusion is critical. However, empirical studies on the relationship between financial inclusion and the interest rate of monetary policy transmission are few; as a result, this study examined the impact of financial inclusion on the effectiveness of the interest rate channel of monetary policy transmission in West Africa. The study employed a panel dataset of 15 West African countries for 2005 and 2020. The data were from secondary sources, particularly the World Bank's World Development Indicator database. The analysis involves descriptive statistics and inferential analysis of the Generalized Method of Moments (GMM) approach. The result of the GMM showed that financial inclusion improves the effectiveness of the interest rate channel of monetary policy transmission. Based on findings, this study recommends that policy authorities in West Africa should embark on a renewed commitment to ensuring access for all in West Africa.